P077 LONG-TERM CLINICAL OUTCOMES OF AN ANTIBIOTIC-COATED NON-CROSSLINKED PORCINE ACELLULAR DERMAL GRAFT IN HIGH-RISK ABDOMINAL WALL RECONSTRUCTION. (25th November 2021) - Robinson, Jordan; Sulzer, Jesse; Baker, Erin; Iannitti, David
Abstract: Aim: Abdominal wall reconstruction in high-risk and contaminated cases remains a challenging surgical dilemma. We report long-term clinical outcomes for a rifampin/minocycline-coated acellular dermal graft (XenMatrix™ AB) in complex abdominal wall reconstruction for patients with a prior open abdomen or contaminated wounds. Material and Methods: Patients undergoing abdominal wall reconstruction at our institution at high risk for surgical site occurrence and reconstructed with XenMatrix™ AB with intent-to-treat between 2014 through 2017 were included. Demographics, operative characteristics, and outcomes were collected. Primary outcome was hernia recurrence. Secondary outcomes included length of stay, surgical site occurrence, readmission, morbidity, and mortality. Results: Twenty-two patients underwent abdominal wall reconstruction using XenMatrix™ AB during the study period. Two patients died while inpatient from progression of their comorbid diseases and were excluded. Sixty percent of patients had an open abdomen at time of repair. All patients were Modified VHWG class 2 or 3. There was a total of four 30-day infectious complications including superficial cellulitis/fat necrosis (15%) and one intraperitoneal abscess (5%). No patients required re-operation or graft excision. Median clinical follow-up was 35.1 months with a mean of 32.2 +/- 16.5 months. Two asymptomatic recurrences and one symptomatic recurrence were noted during this period. Follow-up was extended by phone interview which identified no additional recurrences at a median of 45.5 and mean of 50.5 +/-12.7 months. Conclusions: We present long-term outcomes for patients with high-risk and contaminated wounds who underwent abdominal wall reconstruction reinforced with XenMatrix™ AB to achieve early, permanent abdominal closure. Acceptable outcomes were noted.